Treatment errors resulting from use of lasers and IPL by medical laypersons: results of a nationwide survey - Hammes, Stefan; Raulin, Christian (Journal der Deutschen Dermatologischen Gesellschaft, 2013)
Background: The demand for hair and tattoo removal with laser and IPL technology (intense pulsed light technology) is continually increasing. Nowadays these treatments are often carried out by medical laypersons without medical supervision in franchise companies, wellness facilities, cosmetic institutes and hair or tattoo studios. This is the first survey is to document and discuss this issue and its effects on public health. Patients and methods: Fifty patients affected by treatment errors caused by medical laypersons with laser and IPL applications were evaluated in this retrospective study. We used a standardized questionnaire with accompanying photographic documentation. Among the reports there were some missing or no longer traceable parameters, which is why 7 cases could not be evaluated. Results: The following complications occurred, with possible multiple answers: 81.4% pigmentation changes, 25.6% scars, 14% textural changes and 4.6% incorrect information. The sources of error (multiple answers possible) were the following: 62.8% excessively high energy, 39.5% wrong device for the indication, 20.9% treatment of patients with darker skin or marked tanning, 7% no cooling, and 4.6% incorrect information. Conclusions: The causes of malpractice suggest insufficient training, inadequate diagnostic abilities, and promising unrealistic results. Direct supervision by a medical specialist, comprehensive experience in laser therapy, and compliance with quality guidelines are prerequisites for safe laser and IPL treatments. Legal measures to make such changes mandatory are urgently needed.
First published: 29 November 2012
Gesehen am 28.06.2018